Shear-induced aggregation of amyloid β (1–40) in a parallel plate geometry. Issue 17 (22nd November 2021) - Sharma, Laipubam Gayatri; Pandey, Lalit M.
Abstract: Protein aggregation is induced by various environmental or external factors and associated with various neurodegenerative diseases. Among various external factors, shear stress is inevitable for both in vivo and in vitro applications of proteins. In this study, Aβ (1–40) peptide, a derivative of the amyloid precursor protein, was subjected to constant (300, 500, 700 s −1 ) and varying (ramp) shear in a parallel plate geometry to explore the implications of shear in terms of macro (viscosity) and micro (secondary structure, morphology) characteristics. Aβ (1–40) solution followed a shear thickening flow behaviour with performance index value ' n ' of 2.12. The fibrillation process resulting from the shear force was evaluated in terms of dissipation energy, which was found to exceed the free energy of unfolding. This resulted in the formation of β-sheet rich structures, which were confirmed by CD and FTIR analyses and enhanced Th-T fluorescence. The apparent rate of aggregation ( k ) was found to increase with the shear rate, and inversely related to the solution viscosity. The maximum k value was 0.21 ± 0.3 min −1 at 700 s −1 . The molecular weights of aggregates were determined using gel filtration, which were proportionally related to the solution viscosity. The average molecular weights were estimated to be 70, 62 and 52 KDa for samples sheared at 300, 500 and 700 s −1, respectively. The present study has deciphered the interplay of viscosity, a fluid property, with the aggregation process and its corresponding change in the secondary structures of the peptide. These findings provide useful insights for understanding various proteopathies under shear force. Communicated by Ramaswamy H. Sarma